تطوير ممارسات الادخار التعاوني" أداشي" وإمكانية تطبيقها في المصارف الإسلامية : شمال نيجيريا نموذجا - عمر، يهوذا حسين (Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2016)
Adashi funding is defined in this study as an informal agreement, in both individual and group form, between a number of people in which, in its most famous form, they agree to collect a certain amount of money at a specified time and give the cumulative amount to one member in a circle until each member of the group receives the cumulative amount gathered at a particular time. The study aims at highlighting the significance of traditional Adashi saving or financing and also evaluate people's response to it and the benefits they draw from it in solving personal financial problems, making investments, buying properties (such as houses and cars), or even raising capital for businesses. The study also attempts to examine its development and the viability of proposing it (Adashi) as a new product to Islamic banks particularly in the northern part of Nigeria. In arriving at the conclusion of the study, the researcher critically and analytically used library resources as well as survey techniques by interviewing some scholars, economists, bankers, accountants, and a number of Adashi participants and organizers. Based on critical discussion of references from Islamic jurisprudence on which the legitimacy of Adashi could be established and what could and could not be driven out of it, the study suppots the legitimacy of Adashi transaction. Moreover, the study also finds out that the Adashi organizer, as a trustee of the Adashi fund, can be considered as Ajeer Mushtarak which is lawful for him to be paid for his role in organizing and managing the transaction. The study concludes that other Islamic financial products, such as Murabahah, Tawarruq and Takaful are not more lawful than Adashi. Finally, the possibility of implementing Adashi by Islamic banks in other places and how they (Islamic banks) would benefit from it is also recommended by the study.